Brazilian Scale for Evaluation of Mental Health Care Needs: Additional Evidence - Joana Moscoso Teixeira de Mendonça; Flavio Rebustini; Ana Alice Freire de Sousa; Ilana Eshriqui; Daiana Bonfim; Leticia Yamawaka de Almeida (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To investigate validity evidence of the Brazilian Scale for Evaluation of Mental Health Care Needs (CuidaSM). METHODS This is a psychometric study, which seeks additional evidence of internal structure. Data collection was carried out in 11 Primary Health Care (PHC) services , which implement the Health Care Planning (HCP) methodology, distributed across the five Brazilian regions. The preliminary version of CuidaSM, containing a block self-referred by the user and another block evaluated by PHC professionals, was applied to users aged 18 or over who attended the PHC services for consultation with a higher education professional. The techniques of confirmatory factor analysis and network analysis were used to investigate validity evidence. For the primary data of the confirmatory factor analysis, the factorial loads and the item's predictive power (R2) were used. Six model adjustment indices were adopted and reliability was measured by three indicators using Bayesian estimation. RESULTS A total of 879 users participated in the study. By confirmatory factor analysis, factorial loads ranged from 0.43 to 0.99 and R2 from 0.19 to 0.98. Both the primary indicators and the model adequacy indices were established at satisfactory and consistent levels. The network analysis showed that the items were appropriately associated with their peers, respecting the established dimensions, which again indicates the sustainability and stability of the proposed model. CONCLUSIONS The study findings confirm a consistent and reliable model of the instrument, through a combination of techniques. Considering the importance of using solid instruments in clinical practice, CuidaSM is a promising tool for population-based management and network care organization, aligned with HCP proposals.